Rate of Pneumothorax in Patients Undergoing Large Volume Thoracocentesis - Ali Raza Khan, Khalid Ali, Syed Mazhar Ali Naqvi, Muhammad Sarfraz, Naeem Ashraf, Saba Pervaiz (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of pneumothorax in patients undergoing large volume thoracocentesis. Study Deign: Prospective study Place and Duration of Study: Methodology: One hundred and twenty patients of both genders were presented in this study. Patients were aged between 18 to 75 years of age. Patients details demographics age, sex and body mass index were recorded after taking informed written consent. Ultrasound was performed among all patients to diagnosed pleural effusion >1000 ml. Patients were underwent for thoracocentesis in large volume. Outcomes were prevalence of pneumothorax and amount of fluid aspirated were assessed. Results: Seventy (58.3%) patients were males and 50 (41.7%) were female patients. Mean age of the patients was 36.9±13.65 years with mean BMI 25.7±6.26 kg/m2. Frequency of pneumothorax was 22 (18.3%) and was increases with a number of multiple attempts by passing needle. Among 22 cases, 4 (18.2%) patients had pneumothorax by passing single needle for fluid aspirated. Conclusion: Frequency of pneumothorax was high in patients with thoracentesis. In these instances, the risk of pneumothorax was mostly determined by the quantity of pleural fluid that was removed.